Peran Orang Tua Mengakselerasi Pembelajaran Daring Untuk Menguatkan Mental Spiritual Siswa Kelas V SD Dana Punia Singaraja - Luh Asli; Ni Nyoman Suastini; I Nengah Dwi Endra Suanthara; Ida Ayu Ketut Surya Wahyuni (Jurnal Penelitian Agama Hindu, 2022)
This study aims to examined the form of accelerating the role of parents in online learning during the Covid-19 pandemic and to examined the mental and spiritual impact of the role of fifth graders at Dana Punia Singaraja Elementary School. This research was a mixed research model, namely quantitative and qualitative research, with the research subjects being students of SD Dana Punia Singaraja. The method of determining the sample used was the study population method, which is examining all 17 students. While the data collection methods used were questionnaires, interviews, observation and document recording. Data analysis used quantitative and qualitative descriptive analysis. Based on the results of the analysis obtained the following findings. The role of parents in accelerating online learning contributes very significantly in strengthening students' spiritual mentality. Classically, the role of parents was 85.65%. In detail, it can be seen in each aspect, namely 1) aspects of democratic services by 76.76%, 2) functions of parents (birth, care, education, raising) of 80.82%, 3) control aspects of 85.18%, and 4) attention aspect of 85.65%. Mental spirituality as a result of the role of parents in accelerating online learning classically was 85.06% very good. While the results of each mental spiritual aspect were obtained 1) mental aspects related to the school community amounted to 85.06%, 2) mental aspects related to value alignment of 85.18%, 3) aspects related to the school environment amounted to 76.06 %, 4) aspects related to self-commitment were 76.41%. The results of this study were equipped with suggestions and recommendations.